Methicillin-resistant Staphylococcus aureus acquisition in healthcare workers with cystic fibrosis: a retrospective cross-sectional study. Issue 1 (December 2016) - Wood, Michelle; Sherrard, Laura; Ramsay, Kay; Yerkovich, Stephanie; Reid, David; Kidd, Timothy; Bell, Scott
Abstract Background People with cystic fibrosis (CF) may work in healthcare settings risking nosocomial pathogen acquisition. The aim of this study was to determine the incidence of methicillin-resistantStaphylococcus aureus (MRSA) infection in adult healthcare workers with CF (HCWcf). Methods Data was collected in this observational study on MRSA acquisition from 405 CF patients attending an adult CF centre in Australia between 2001–2012. Demographic and clinical characteristics were compared between HCWcf and non-HCWcf. A sub-analysis was subsequently performed to compare demographic and clinical characteristics between those patients (HCWcf versus non-HCWcf) that acquired MRSA. We also investigated rates of chronic MRSA infection and the outcome of eradication treatment in HCWcf. Results A higher proportion of HCWcf acquired MRSA [n  = 10/21] compared to non-HCWcf [n  = 40/255] (P <0.001). The odds of MRSA acquisition were 8.4 (95 % CI, 3.0 – 23.4) times greater in HCWcf than non-HCWcf. HCWcf with MRSA were older (P  = 0.02) and had better lung function (P  = 0.009), yet hospitalisation rates were similar compared to non-HCWcf with MRSA. Chronic MRSA infection developed in 36/50 CF patients (HCWcf, n  = 6; non-HCWcf, n  = 30), with eradication therapy achieved in 5/6 (83 %) HCWcf. Conclusions The rate of MRSA incidence was highest in HCWcf and the workplace is a possible source of acquisition. Vocational guidance should include the potential for MRSA acquisition for CF patients considering healthcare professions.